Ancient felsic sediments recycled through the deep mantle by plate tectonics - Bradley J. Peters; Marc C. Halfar; Courtney J. Rundhaug; Paterno R. Castillo; Maria Schönbächler (Proceedings of the National Academy of Sciences, 2026)
Many petrological, geodynamical, and geochemical perspectives have offered circumstantial evidence for either an early onset of plate tectonics in the first 10% of Earth’s history or a late onset after the great oxidation event (2.5 Ga ago). This calls into question over what timescales plate tectonics have influenced terrestrial geological and geochemical processes. We present geochemical data from the products of ancient crustal subduction, which were recycled into the deep mantle and then tapped by the modern Marquesas volcanic hotspot. We demonstrate that these materials have distinct short-lived radiogenic ( 146 Sm- 142 Nd, t 1/2 = 103 Ma) isotopic compositions (average μ 142 Nd = +2.3 ±1.3, n = 3) compared to other Marquesas lavas (average μ 142 Nd = −0.8 ±1.2, n = 7). These results require that the history of these subduction products diverged from those of other Marquesas magmas more than four billion years ago. Quantitative modeling suggests that the most geochemically enriched Marquesas samples represent up to ~0.6% recycled crustal sediments, which may have been subducted at any time in Earth’s history but were most likely subducted in the late Hadean Eon to early Eoarchean Era. The inferred felsic composition of such materials further requires that both crustal melting and sedimentation processes were active in some form on the early Earth. Further, the preservation of evidence for foundational planetary events in geologically young rocks reveals that Earth’s volcanic hotspots could provide a defining perspective on the early planetary-scale processes that build Earth-like planets.